2021
DOI: 10.21161/mjm.211115
|View full text |Cite
|
Sign up to set email alerts
|

Serogroups and antibiogram of Salmonella isolates from dairy cattle in Nkonkobe District, South Africa

Abstract: Aims: The use of antimicrobial agent for treatment or growth promotion has added burden to treat infection diseases caused by pathogenic bacteria as they can acquire resistance. Salmonella is one of the major zoonotic bacterial pathogens that acts as a potential reservoir of antimicrobial resistance elements. In this study, the presence of Salmonella serotypes and the antibiogram patterns of the isolates from fecal samples of healthy cows in some selected localities in Eastern Cape, South Africa were studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Other commonly used antibiotic such as erythromycin and cefuroxime had a 40% resistance which was high. Although, earlier report by many authors in Nigeria working in different research areas [28,29,30,31,32] have reported antibiotic abuse and high prevalence of self-medication with antibiotics as being responsible for the selection of antibiotic resistant bacterial strains. This may not be the only reason for the increase in resistance observed.…”
Section: Discussionmentioning
confidence: 97%
“…Other commonly used antibiotic such as erythromycin and cefuroxime had a 40% resistance which was high. Although, earlier report by many authors in Nigeria working in different research areas [28,29,30,31,32] have reported antibiotic abuse and high prevalence of self-medication with antibiotics as being responsible for the selection of antibiotic resistant bacterial strains. This may not be the only reason for the increase in resistance observed.…”
Section: Discussionmentioning
confidence: 97%